1973
DOI: 10.1055/s-0028-1098243
|View full text |Cite
|
Sign up to set email alerts
|

First Laser Endoscopy via a Fiberoptic Transmission System

Abstract: For the first time it was possible to transmit a powerful laser beam (6 watt argon laser) through the biopsy channel of a conventional endoscope. This was achieved by the development of a special quartz fiberoptic transmission system, consisting of a single very flexible fiber with a diameter of 150 p. A strong absorption effect on liver tissue was observed with the argon laser, due to selective colour absorption of hemoglobin in the green-blue spectral region. The effect on the intact liver surface was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1975
1975
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…At about the same time, Dwyer et al [5], Kiefhaber et al [6], and Fruhmorgen et al [7] per formed successful hemostasis in humans. The initial reports were from uncontrolled series but were worthy of notice.…”
Section: Control Of Acute Hemorrhagementioning
confidence: 96%
See 1 more Smart Citation
“…At about the same time, Dwyer et al [5], Kiefhaber et al [6], and Fruhmorgen et al [7] per formed successful hemostasis in humans. The initial reports were from uncontrolled series but were worthy of notice.…”
Section: Control Of Acute Hemorrhagementioning
confidence: 96%
“…The largest series of patients with esopha geal carcinoma treated by laser therapy is by Fleischer [6], He selected patients who were not considered to be curable by any conven tional treatment. In all patients the goal of therapy was palliation.…”
Section: Treatment Of Ugi Neoplasmsmentioning
confidence: 99%
“…In 1970 Goodale et al 15 were the first to use a CO 2 laser through a rigid endoscope to coagulate bleeding gastric ulcers. In 1973 Nath et al 25 reported the first use of a flexible fi- beroptic endoscope along with an argon laser. However, the long wavelength of the CO 2 laser results in an excessive loss of power when transmitted through conventional solid fiberoptic cables, thus preventing its use in this manner.…”
Section: Enthusiasm Temperedmentioning
confidence: 99%
“…The development of flexible light guides by Naht et al, in 1973 [19] and Kiefhaber et al [16] meant a decisive breakthrough in the field of flexible endo scopes. Laser-induced hemostasis in the gastrointestinal tract was performed for the first time by means of flexible gastroscopes in 1975 [7,11,16].…”
Section: Introductionmentioning
confidence: 99%